1979
DOI: 10.1086/283481
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Variables Affecting the Dispersal Behavior of Drosophila pseudoobscura and Its Relatives

Abstract: One of the earliest attempts to measure and incorporate dispersal into an understanding of population genetic structure was made by Dobzhansky and Wright (1943). They performed release-recapture studies with laboratory-reared mutant Drosophila pseudoobscura. More recent studies of the same species (Powell et al. 1976;Crumpacker and Williams 1973) have employed improved methods which allow marking of native flies.In their early studies Dobzhansky and Wright assumed that flies were equally likely to move from or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

1979
1979
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 14 publications
(30 reference statements)
0
24
1
Order By: Relevance
“…Dobzhansky & Powell (1974) found that for D. pseudoobscura, 19. persimilis, D. azteca and D. miranda variances after the 1 day were on the average of 21449 m 2 and in PoweR, Dobzhansky, Hook & Wistrand (1976) these variances are even greater between 40000 and 100 000 m 2 . Their estimates of Wright's mean square are by far greater than those reported for D. pseudoobscura in the early papers (Dobzhansky & Wright 1943, 1947.…”
Section: Datementioning
confidence: 99%
See 1 more Smart Citation
“…Dobzhansky & Powell (1974) found that for D. pseudoobscura, 19. persimilis, D. azteca and D. miranda variances after the 1 day were on the average of 21449 m 2 and in PoweR, Dobzhansky, Hook & Wistrand (1976) these variances are even greater between 40000 and 100 000 m 2 . Their estimates of Wright's mean square are by far greater than those reported for D. pseudoobscura in the early papers (Dobzhansky & Wright 1943, 1947.…”
Section: Datementioning
confidence: 99%
“…Table 3 Dispersal parameters: d, aD.F., °B.M., mean distance r-, and WRIGHT's average distance i-w = I;r 2 f(r.rf+e/2,r) in metres; ~, variance or ~, Wrighrs mean square distance o= w = ~r 3 f/(~rf+e/2tr) in metres-squared. Begon (1976) and Dobzhansky & Powell (1974), which are reported in Table 3. Let qi be the probability that a marked fly reaches the i th annulus.…”
Section: Radius Datementioning
confidence: 99%
“…Dispersal of Drosophila is affected by changing temperature under natural conditions (Dobzhansky and Wright 1943;Dobzhansky et al 1979;Dubinin and Tiniakov, 1954;Johnston and Heed, 1976;Powell et al 1976). From this study temperature-influenced emigration behavior of D, melanogaster in a population, which was evaluated with Sakai's migration system, seems to at least reflect the genetic variation of vagility for flies under changing temperature conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Movement of Drosophila, indeed, is affected by temperature in natural environments (Dobzhansky and Wright,1943 ;Dobzhansky et al 1979;Dubinin and Tiniakov, 1946;Dyson-Hudson, 1956;Johnston and Heed, 1976;Powell et al 1976). Emigration behavior of D. melanogaster measured by Sakai's migration system is a polygenic character (Mikasa and Narise, unpublished data), and is also affected by temperature (Tantawy et al 1975;Narise 1979, 1983 a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Movement of Drosophila from one place to another is related to feeding, oviposition, search for a mate, and avoidance of deleterious conditions. Environmental factors such as temperature, light, wind, and different habitat conditions also influence the movement of Drosophila Wright, 1943, 1947;Burla et al, 1950;Dyson-Hudson, 1956;Koch, 1967;Dobzhansky and Powell, 1974;Richardson and Johnston, 1975;Johnston and Heed, 1976;Powell et al, 1976;Dobzhansky et al, 1979). Because of the interactions among the above factors under natural conditions, it is very difficult to detect directly which biological and environmental factors influence the movement of flies in nature.…”
Section: Introductionmentioning
confidence: 99%